Dextran successful carrier molecule for the delivery of NSAIDs with reduced gastrointestinal effect - Shrivastava P.K.; Singh R.; Shrivastava S.K. (My University, 2025)
The dextran ester polymeric prodrug of aceclofenac and mefenamic acid was synthesized through carbonyldiimidazole coupling agent. The prepared polymeric prodrug was characterized by UV, IR, X-RD and 1H NMR. The in vitro hydrolysis study was performed by HPLC and polymeric conjugate subjected for in vitro hydrolysis showed negligible hydrolysis in simulated gastric fluid pH 1.2 for 3 h. The half-life of the aceclofenac dextran conjugate in simulated intestinal fluid (SIF) pH 7.4 and phosphate buffer solution (PBS) pH 9.0 was found to be 8.51 h and 33.72 min, respectively. The half-life 4.66 h and 25.4 min was found in SIF pH 7.4 and PBS pH 9.0, respectively for mefenamic acid conjugates. The conjugates were screened for biological activity such as anti-inflammatory, analgesic and ulcerogenic activity. The statistical data obtained from the biological experiment suggested that the value was found to be significant with respect to normal control.